Prevalence of DDC genotypes in patients with aromatic L-amino acid decarboxylase (AADC) deficiency and in silico prediction of structural protein changes - ÖZTÜRK HİŞMİ, BURCU (My University, 2023)
Aromatic L-amino acid decarboxylase (AADC) deficiency is a rare autosomal recessive genetic disorder affecting the biosynthesis of dopamine, a precursor of both norepinephrine and epinephrine, and serotonin. Diagnosis is based on the analysis of CSF or plasma metabolites, AADC activity in plasma and genetic testing for variants in the DDC gene. The exact prevalence of AADC deficiency, the number of patients, and the variant and genotype prevalence are not known. Here, we present the DDC variant (n = 143) and genotype (n = 151) prevalence of 348 patients with AADC deficiency, 121 of whom were previously not reported. In addition, we report 26 new DDC variants, classify them according to the ACMG/AMP/ACGS recommendations for pathogenicity and score them based on the predicted structural effect. The splice variant c.714+4A>T, with a founder effect in Taiwan and China, was the most common variant (allele frequency = 32.4%), and c.[714+4A>T];[714+4A>T] was the most common genotype (genotype frequency = 21.3%). Approximately 90% of genotypes had variants classified as pathogenic or likely pathogenic, while 7% had one VUS allele and 3% had two VUS alleles. Only one benign variant was reported. Homozygous and compound heterozygous genotypes were interpreted in terms of AADC protein and categorized as: i) devoid of full-length AADC, ii) bearing one type of AADC homodimeric variant or iii) producing an AADC protein population composed of two homodimeric and one heterodimeric variant. Based on structural features, a score was attributed for all homodimers, and a tentative prediction was advanced for the heterodimer. Almost all AADC protein variants were pathogenic or likely pathogenic.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; GENETİK VE KALITIM; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; ENDOCRINOLOGY & METABOLISM; BIOCHEMISTRY & MOLECULAR BIOLOGY; GENETICS & HEREDITY; Endokrinoloji, Diyabet ve Metabolizma; Biyokimya; Moleküler Biyoloji; Genetik; Endokrinoloji; Endocrinology, Diabetes and Metabolism; Biochemistry; Molecular Biology; Genetics; Endocrinology; ACMG; Dopamine; Neurotransmitter disorder; Serotonin; Variant effect prediction